Benzothiazole Derivatives as Multifunctional Antioxidant Agents for Skin Damage: Structure-Activity Relationship of a Scaffold Bearing a Five-Membered Ring System - Ernestine Nicaise Djuidje; Riccardo Barbari; Anna Baldisserotto; Elisa Durini; Sabrina Sciabica; Jan Balzarini; Sandra Liekens; Silvia Vertuani; Stefano Manfredini (MDPI AG, 2022)
Skin diseases often give multifactorial damages; therefore, the development of multifunctional compounds represents a suitable approach especially against disorders that are induced by oxidative stress. Thus, taking into account the successful results we achieved on benzimidazoles, we have devised a new series of isosteric benzothiazoles and investigated their antioxidant, photoprotective, antifungal and antiproliferative activity. Particular attention has been paid to synergistic antioxidant and photoprotective properties. For compounds 9a and 10a, a multifunctional profile was outlined, supported by an excellent filtering capacity, mainly UVB, which has higher capacities than those of the reference PBSA which is currently in the market as a UV sunscreen filter. The two compounds were also the best in terms of growth inhibition of dermatophytes and Candida albicans, and 10a also showed good antioxidant activity. Furthermore, 9a was also effective on melanoma tumor cells (SK-Mel 5), making these compounds good candidates in the development of new skin protective and preventive agents.